(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
this article reflects on ways to improve the effectiveness of education in teaching batanika. Today’s modern education cannot be imagined without interactive techniques. Active methods that reveal the content of the lesson serve as practical support for both the student and the educator. In contrast to the traditional lesson, methods are invigorating the course process, and most importantly the student is cultivating consciousness. The article also analyzes the importance of these techniques by conducting research based on samples. In the current educational system, ways of organizing cognitive activity of students are analyzed in improving educational effectiveness in teaching the new conceptual technology of knowledge acquisition and biology.